Erratum to: Activity and diffusivity of oxygen in the liquid dilute BixSb1-x solutions - Editorial (Journal of Mining and Metallurgy. Section B: Metallurgy)
This erratum concerns a correction in the author name, in the abstract and in the text of the original article. Link to the corrected article 10.2298/JMMB180311014J